STRATEGI GURU DALAM MENGEMBANGKAN SIKAP TOLERANSI MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA DI SMP NEGERI 2 BANJARMASIN - Aulia, Vivi; Sarbaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the development of mutual respect as a component in character building for students in dealing with differences at school. However, mutual respect among students still varies, requiring teachers to develop effective methods through Pancasila Education. The purpose of this study is to describe the methods used by teachers, identify the values ​​of mutual respect they instill, and evaluate students' understanding after participating in the learning process at SMP Negeri 2 Banjarmasin. This study employed qualitative methods with a descriptive approach. Data were collected through observation, interviews, and documentation. The subjects were Pancasila Education teachers and students of SMP Negeri 2 Banjarmasin. Data analysis was conducted through reduction, presentation, and conclusion drawing. Data validity was tested using source and technique triangulation. The research results show that teachers' strategies for developing tolerance include integrating tolerance values ​​into learning, providing role models, and using active methods such as discussions and group work. The values ​​developed include appreciating differences, mutual respect, cooperation, and non-discrimination. Students' understanding of tolerance increased despite individual differences. Therefore, it is recommended that teachers continue to develop innovative learning strategies and strengthen the inculcation of tolerance values ​​in the school environment.